PENGARUH LAMA PERENDAMAN BUBU BESI TERHADAP HASIL TANGKAPAN IKAN NILA DI DANAU KERINCI PROVINSI JAMBI - Lisna Lisna; Amallya Amallya; Indra Sulaksana; Fauzan Ramadhan (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
Koto Petai Village is one of the villages near Lake Kerinci, especially in Danau Kerinci District, fishing activities in Koto Petai are carried out in the morning and evening according to the fishing gear used by the local community. The fishing gears found in Koto Petai village are tangkul / pesap, gill nets, nets, stick charts and traps.The aims of this study was to determine the differences in the catch of tilapia and to determine the composition of the catch in the form of weight, number and type of fish caught against the soaking time of the traps.The research method used is the experimental fishing method and the data analysis used in this study was a completely randomized design analysis (CRD). The results of the analysis of variance show that soaking time treatment had a doesn’t significant effect on the average weight to the whole catch,Meanwhile, the catch of tilapia does not significantly affect the immersion time and result of Duncan test showed that the weight of the catch of immersion for 8 hours10 hours and for 12 hourswas not significantly different (P >0.05) .Based on research that has been done inconclude that long ago soaking iron fish trap for 8 hours resulting in a more optimal catch the most caught fish is tilapia.